Aboveground biomass and carbon storage relationship of Turkish pines - Durkaya, Ali Kemal; Durkaya, Birsen; Makineci, Ender; Orhan, Ibrahim; Durkaya, Birsen; Durkaya, Ali (Parlar Scientific Publications parlar@masell.com, 2015)
Data related to carbon storage capacities of forests have become increasingly important in the context of global warming. Following the Kyoto Protocol, countries need to understand the carbon storage abilities of their forests in order to perform true declarations. So, we aimed to design allometric biomass and carbon equations able to predict above-ground biomass and amount of carbon, and to enable the conversion of standing stem volumes to stored carbon values of above-ground tree components for Pinus brutta Ten, P. nigra Arn. and P. sylvestris L. trees. Carbon concentrations of tree components were established using tree samples. The biomass and sequestered carbon were modeled from the standing stem volume of single trees, in order to allow the calculation of the carbon sequestered in stands. The study tested different models in determining biomass as a function of DBH or DBH and H. Appropriate functions were chosen and used in the estimation of biomass. The present study makes it possible to safely attain above-ground biomass and sequestered carbon values without any auxiliary operation by using the standing stem volume, which is the most practical element in management plans. © 2017 Elsevier B.V., All rights reserved.
Keywords: Above-Ground Biomass; Carbon Concentration; Carbon Storage; Pinus Brutte Ten.; Pinus Nigra Am.; Pinus Sylvestris L; Stem Volume